2016
DOI: 10.1016/j.jneb.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Worksite Diabetes Prevention Intervention on Diet Quality and Social Cognitive Influences of Health Behavior: A Randomized Controlled Trial

Abstract: Objective To evaluate the impact of a worksite diabetes prevention intervention on secondary outcomes regarding the change in diet quality and components of the Health Action Process Approach (HAPA) theoretical framework Design Pretest-posttest control group design with 3-month follow-up Setting University worksite Participants Employees 18–65 years old with prediabetes (n=68) Intervention 16-week group-based intervention adapted from the Diabetes Prevention Program Main Outcome Measures Diet quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 31 publications
(38 reference statements)
4
43
2
Order By: Relevance
“…As older age correlated with fewer expected disadvantages, these results could be tentatively interpreted that due to family (whether married or not) and work commitments younger adults may perceive increasing PA as a further demand on their resources and thus with more disadvantages. These results are in accordance with previous research (Bandura, 1996; Burgess et al, 2017; Goode et al, 2016; Miller et al, 2016), and suggest that even after successful weight loss, younger age and expected disadvantages of behavior change are associated with early attrition. Furthermore, as marriage is associated with higher social support (Burgess et al, 2017; Soulsby & Bennett, 2015), these results suggested that being older person in a marriage may potentially lead to higher social support for behavior change.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As older age correlated with fewer expected disadvantages, these results could be tentatively interpreted that due to family (whether married or not) and work commitments younger adults may perceive increasing PA as a further demand on their resources and thus with more disadvantages. These results are in accordance with previous research (Bandura, 1996; Burgess et al, 2017; Goode et al, 2016; Miller et al, 2016), and suggest that even after successful weight loss, younger age and expected disadvantages of behavior change are associated with early attrition. Furthermore, as marriage is associated with higher social support (Burgess et al, 2017; Soulsby & Bennett, 2015), these results suggested that being older person in a marriage may potentially lead to higher social support for behavior change.…”
Section: Discussionsupporting
confidence: 92%
“…Lifestyle interventions aim for healthy behaviors to become intrinsically regulated, that is, being rewarding in itself instead of being performed to avoid, for example, a guilty conscience (introjected regulation) or due to external demands (extrinsic motivation; Ryan & Deci, 2000). The formation of new lifestyle habits is also supported by strong self‐efficacy, that is, beliefs about abilities (Bandura, 1996; Miller, Weinhold, & Nagaraja, 2016), and expected outcomes so that expected advantages increase the likelihood of a behavior being performed (Miller et al, 2016). Temptations, such as viewing television instead of exercising, describe commonly cited reasons for sedentary lifestyle, and appear to be especially important in impeding adherence to newly acquired behaviors (Hausenblas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, those whose diet improved reported an increase in their diet quality score by an average of 8.8 points, resulting in a mean score greater than the sample mean at Survey 7. Contextually, intervention studies reported changes in diet quality scores among people at risk of type 2 diabetes mellitus of +4.3 points using the ARFS (p < 0.01 for between group differences) [22], and +4.6 points using the Alternative Healthy Eating Index (p < 0.01 for within group differences) [23]. The increase in diet quality in the current study can be at least partly explained by some women who had poor diets at baseline becoming lost to follow up, as baseline ARFS total scores were lower for women who died, withdrew from the study or became frail, compared with women who completed Survey 7.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated changes in diet quality as assessed using an a priori defined diet quality index or score, or intakes of individual food groups. Miller et al[ 12 ] reported significant within group improvements in overall diet quality scores (+4.6, P < 0.01) measured using the Alternative Healthy Eating Index following a 4-mo group-based diabetes prevention program. In another study, Block et al[ 11 ] reported changes in food habits associated with higher diet quality, such as significant changes in the consumption frequency of fruits and vegetables (increases) and sweets and refined carbohydrate foods (decreases) found among those with prediabetes who received a 6-mo automated web-based diabetes prevention program.…”
Section: Discussionmentioning
confidence: 99%
“…Specific dietary changes following the diabetes prevention programs have included a reduction in total energy intake and favourable shifts in macronutrient composition ( e.g ., reduction in total and saturated fat intake)[ 9 ]. Only recently have changes in diet quality or amounts of foods (as opposed to energy or nutrients) been reported both immediately following completion of the intervention[ 11 , 12 ], as well as over the long-term for periods of 5-10 years later[ 13 , 14 ]. To date, no studies have reported the effect on diet of a diabetes prevention program tailored for men.…”
Section: Introductionmentioning
confidence: 99%